Diacylglycerol Kinases: Regulation and Signaling Roles - Topham, Matthew K.; Prescott, Stephen M. (Thrombosis and Haemostasis, 2002)
Diacylglycerol kinases (DGKs) are thought to attenuate diacylglycerol signals by converting diacylglycerol to phosphatidic acid. The nine mammalian diacylglycerol kinases that have been identified are widely expressed, but each isoform has a unique tissue and subcellular distribution. The activity of DGKs is regulated by mechanisms that can modify their access to diacylglycerol, affect their activity, or alter their ability to bind to other proteins. Although little is known of the specific function of DGKs in platelets, they likely influence actin reorganization and other signaling events requiring diacylglycerol.
Keywords: Diacylglycerol kinases; diacylglycerol; phosphatidic acid